Transparency in E-Participation Management through the SIMONAS Application: The Impact of Trust, Legitimacy and Accountability of the Jakarta Provincial Parliament - Artanti Paramesti; Nurdin (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
This study aims to analyze Jakarta citizens' e-participation in e-government initiatives through the SIMONAS application to achieve transparency and efficiency in managing public aspirations at the Jakarta Provincial Parliament (DPRD). Using a descriptive qualitative method, this study evaluates the working mechanisms, challenges, and impacts of implementation based on theories of transparency and digital government efficiency. The results indicate that the SIMONAS application has improved public information openness online and integrated internal workflows between departments. The transparency of e-participation management is proven to increase public trust, evidenced by the resolution of aspirations by the DPRD. This implementation reflects the DPRD's political commitment to accommodating public input for regional policies. However, challenges such as low consistency in data updates and overlapping responsibilities were identified. Overall, SIMONAS strengthens the legitimacy and performance of the Jakarta DPRD, although managerial improvements remain necessary for long-term system optimization